C-reactive protein is a more valuable marker in predicting the severity of complications in measles-affected children compared to blood cell count-derived inflammatory indices - Stojiljković, Marija; Miljković, Mirjana (Vojnosanitetski pregled, 2023)
Background/Aim. Measles is a contagious disease with a good prognosis; however, severe complications may some-times develop. C-reactive protein (CRP) and blood cells count-derived inflammatory indices – granulocyte-lymphocyte ratio (GLR), platelet to lymphocyte ratio (PLR), monocyte to lymphocyte ratio (MLR), mean plate-let volume (MPV)/platelet count ratio (MPR), red blood cell distribution width (RDW), and MPV are the indicators related to the clinical outcome in various inflammatory diseases. The aim of the study was to analyze the values of CRP, blood cell count, GLR, PLR, MLR, MPR, RDW, and MPV in measles-affected children compared to healthy controls and between measles-affected children with complicated and severely complicated measles form. A particular aim of the paper was to assess the suitability of inflammatory-derived markers for predicting the severity of the disease. Methods. The study included 55 measles-affected children who developed complications (examination group), while the control group included 30 healthy children. The first peripheral blood count, obtained on the first hospitalization day (before treatment), was used for further analyses. Results. The white blood cells, lymphocytes, monocytes, and platelets count were significantly lower, while GLR, PLR, MPR, and CRP were significantly higher in measles-affected children (p ˂ 0.05). In severely complicated measles form, significantly higher values of granulocytes, CRP, GLR, and PLR were documented, including lower lymphocytes (p ˂ 0.05). A linear regression analysis showed that CRP was the only indicator with pre-dictive significance for the severity of the course of measles. Conclusion. The blood cell count-derived inflammatory indices should not be crucial in assessing the severity of measles in children. CRP was the most valuable predictive factor for the development of the severe course of measles in measles-affected children.
Keywords: blood cells; blood platelets; child; c-reactive protein; leukocytes; measles; prognosis; severity of illness index